Metabolism of the human brain: the principle and limitation of global measurements - Hoyer, Siegfried (Cerebral blood flow and metabolism measurement, 1985)
Global measurements of substrate consumption of any organ are based on the principle of Fick: the amount of a substrate which is used by that organ is represented by the difference in concentrations as measured supplying arterial and releasing venous blood, i.e., the arteriovenous difference. However, some conditions have to be fulfilled for this principle to hold: The arterial and venous concentrations of the substrate and blood flow through the organ have to be constant, and one main vein should drain the blood from the organ. The consumption or release of the substrate may then be calculated from the arteriovenous substrate difference and blood flow.